Fikih Ekonomi Nelayan: Studi Desa Gempolsewu Kabupaten Kendal Jawa Tengah - Nikmah, Umi Jayilatun (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2025)
This article examines the sharing of fish catches in Gempolsewu Village, Kendal Regency, in practice facing challenges of transparency, injustice in the distribution of results, which has the potential to harm one party. By using the empirical normative method. This study found that cooperation between fishermen and ship owners in Gempolsewu Village was carried out through a verbal agreement based on local traditions. This practice resembles the muḍārābah muṭlāqah contract, where ship owners provide capital and fishermen manage the business. This distribution of results is not fully in line with the principles of mu'āmālah fiqh, related to a clear agreement on profit sharing. In general, the distribution of results is 60% for fishermen and 40% for ship owners.